Prognostic Nutritional Index with Wound Complication After Laparotomy in Colorectal Cancer Patients at Dr. Zainoel Abidin General Hospital Banda Aceh - Hadi, Amirul; Yusuf, Muhammad; Naufal, Iflan; Hidayat, Imam (Folia Medica Indonesiana, 2024)
Colorectal cancer patients generally undergo laparotomy as part of the management. The earliest complications of laparotomy are bleeding, surgical wound infection, and anastomotic dehiscence. Albumin-lymphocytes are indicators of nutritional status and inflammation combined in the Prognostic Nutritional Index (PNI). Evaluation of PNI related to the degree of post-laparotomy wounds in colorectal cancer has not been widely explained. Objective: to find out the correlation of PNI for laparotomy wound complications in colorectal cancer patients at Dr. Zainoel Abidin General Hospital Banda Aceh. Method: A cross-sectional study will assess the correlation of PNI to the degree of post-operative wounds with the South Hampton Wound Scale. PNI values were determined by albumin and lymphocytes. The subjects were colorectal cancer patients, aged 18 years and underwent laparotomy. The assessment was carried out on the 7th day after laparotomy. The Spearman test was performed to determine the correlation. Results: 30 colorectal cancer patients as samples, with an average age of 49.43 years old (±11.06), male (56.7%), moderately differentiated adenocarcinoma (46.7%), average albumin 3.08 (±0.47) and lymphocytes 13.93 (±8.22). After evaluation, we found that patients with normal PNI values had South Hampton grade 1 (23.3%), while mild malnutrition was in grade 1 (6.7%) and 2 (6.7%), moderate malnutrition was in grade 3 (23.3%) and grade 4 (16.7%) and severe malnutrition were in grade 4 (16.7%) and grade 5 (13.3%). Conclusion: There was a very strong correlation between PNI and postoperative wound complications in colorectal cancer.